How do Ca2+ ions pass through the sarcoplasmic reticulum membrane. Issue 5 (October 1995) - Mintz, Elisabeth; Guillain, Florent
Abstract : We propose an overview of the mechanism of Ca 2+ transport through the sarcoplasmic reticulum membrane via the Ca 2+ -ATPase. We describe cytoplasmic calcium binding, calcium occlusion in the membrane and lumenal calcium dissociation. A channel-like structure is discussed and related to structural data on the membranous domain of the Ca 2+ -ATPase.